2018
DOI: 10.1007/s11031-018-9689-z
|View full text |Cite
|
Sign up to set email alerts
|

The manageability of empathic (in)accuracy during couples’ conflict: Relationship-protection or self-protection?

Abstract: The current study sought to expand upon research on motivated empathic (in)accuracy by testing assumptions underlying the empathic accuracy model, namely if a perceiver's level of empathic accuracy is variable and might be associated with different outcomes depending the situation. More specifically, the model assumes that (a) the perception of threat in the thoughts/feelings of an interaction partner can result in a lower level of empathic accuracy, and (b) empathic accuracy can both improve and harm situatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Empathic accuracy reflects the ability to recognize the emotions of others (Ickes et al, 1990) and has long been thought to benefit individual and relational well-being (i.e., Ickes, 1997). Numerous studies show that higher levels of empathic accuracy, along with related skills including emotion recognition, are linked to (a) higher levels of well-being such as positive mood (i.e., Hinnekens et al, 2018), happiness (i.e., Furnham & Petrides, 2003), and life satisfaction (i.e., Gannon & Ranzijn, 2005), (b) lower levels of ill-being such as anxiety (i.e., Fernandez-Berrocal et al, 2006) and depression (i.e., Gadassi et al, 2011; cf. Schreiter et al, 2013) and (c) higher levels of relationship satisfaction (i.e., Sened et al, 2017).…”
Section: Empathic Accuracy and Well-beingmentioning
confidence: 99%
“…Empathic accuracy reflects the ability to recognize the emotions of others (Ickes et al, 1990) and has long been thought to benefit individual and relational well-being (i.e., Ickes, 1997). Numerous studies show that higher levels of empathic accuracy, along with related skills including emotion recognition, are linked to (a) higher levels of well-being such as positive mood (i.e., Hinnekens et al, 2018), happiness (i.e., Furnham & Petrides, 2003), and life satisfaction (i.e., Gannon & Ranzijn, 2005), (b) lower levels of ill-being such as anxiety (i.e., Fernandez-Berrocal et al, 2006) and depression (i.e., Gadassi et al, 2011; cf. Schreiter et al, 2013) and (c) higher levels of relationship satisfaction (i.e., Sened et al, 2017).…”
Section: Empathic Accuracy and Well-beingmentioning
confidence: 99%
“…Support for the hypothesis that couples may be motivated to be inaccurate when information is threatening, however, has not been consistently supported. For example, Hinnekens et al (2018) did not find support that empathic accuracy was lower for threatening thoughts and feelings as compared to nonthreatening thoughts and feelings. Additionally, Sened et al's ( 2017) meta-analysis found that empathic accuracy for negative emotions was positively associated with relationship satisfaction, whereas empathic accuracy for positive emotions was not significantly correlated with relationship satisfaction.…”
Section: Discussionmentioning
confidence: 80%
“…However, thoughts and feelings are conceived as separate entities by lay people and have distinctly different linguistic characteristics, such as people using more words to express thoughts than feelings (Ickes & Cheng, 2011). The few studies in which empathic accuracy for thoughts versus feelings were separately assessed also revealed differences in underlying processes (Barone et al, 2005; Hinnekens et al, 2018). Importantly, people seem to pay more attention to nonverbal visual cues and less to verbal cues when inferring feelings than when inferring the thoughts of others (Hall & Schmid Mast, 2007).…”
Section: Empathic Accuracy and Target Expressivitymentioning
confidence: 99%
“…People can be motivated to be more or less empathically accurate (Ickes & Simpson, 2004; Zaki, 2014). Motivated inaccuracy can happen when this inaccuracy protects partners from recognizing information that can destabilize their relationship (Simpson et al, 1995; but note that in Hinnekens et al, 2018 this link could not be replicated). In situations in which one’s partner’s thoughts and feelings are relationship threatening, greater empathic accuracy can hurt the relationship by being personally distressing and raising doubts about the relationship’s viability (Ickes & Simpson, 2004).…”
Section: Empathic Accuracy and Target Expressivitymentioning
confidence: 99%